Stroke symptoms and risk for incident coronary heart disease in the REasons for Geographic And Racial Differences in Stroke (REGARDS) Study - Colantonio, Lisandro D. (Int J Cardiol, 2016)
BACKGROUND: Many adults without cerebrovascular disease report a history of stroke symptoms, which is associated with higher risk for stroke. Because stroke and coronary heart disease (CHD) share many risk factors, we examined the association between a history of stroke symptoms and incident CHD. METHODS: We analyzed data from 8,999 black and 12,499 white REasons for Geographic And Racial Differences in Stroke (REGARDS) study participants without a prior myocardial infarction, stroke or transitory ischemic attack enrolled in 2003-2007 (total participants=21,498, all ≥45 years of age). A history of stroke symptoms (i.e., unilateral weakness, unilateral numbness, full-field vision loss, half-field vision loss, understanding problems and communication problems) was assessed at baseline using the Questionnaire for Verifying Stroke-Free Status. Participants were followed for incident CHD and CHD death through December 2011. RESULTS: Overall, 3,432 (16.0%) participants reported a history of stroke symptoms (1,771 [19.7%] blacks and 1,661 [13.3%] whites). There were 701 incident CHD events including 209 CHD deaths over a median follow-up of 5.8 years. After adjustment for CHD risk factors, hazard ratios (95% confidence interval [95%CI]) for incident CHD associated with reporting any versus no stroke symptoms were 1.26 (1.04-1.51) in the overall population, 1.28 (0.99-1.65) among blacks and 1.23 (0.94-1.61) among whites. Multivariable-adjusted hazard ratios (95%CI) for CHD death associated with any versus no stroke symptoms were 1.50 (1.10-2.06) overall, 1.58 (1.07-2.32) among blacks and 1.41 (0.82-2.43) among whites. CONCLUSION: A history of stroke symptoms is associated with a higher incidence of CHD among black and white adults.